Economy-Wide Impact of Gas Cutoff Commitment in the European Union: A CGE Analysis - Rifa'i, Achmad (Fakultas Ekonomi dan Bisnis Universitas Lampung, 2025)
This paper aims to investigate the potential cessation of gas supply in the European Union (EU) amid Russian-Ukrainian war after the European Commission submitted a proposal to reduce gas supply to all EU member states. To identify economy-wide impact, we apply Computable General Equilibrium (CGE) approach and utilize Global Trade Analysis Project (GTAP) 10 database covering 141 regions and 65 sectors. Our empirical analysis reveals that the gas supply reduction policy will heavily affect EU macroeconomic indicators, including declines in GDP and welfare in all simulations. The trade balance position remains strong, which still recorded a surplus. Nevertheless, the competitiveness (ToT) and export-import performances in the gas sector are turning down. These findings contribute to the geopolitical phenomenon that these tensions caused only declining economic performance at regional and global levels. Therefore, we suggest that any forms of tension and potential political and economic policies that lead to slowing down the economy must be resolved.